7. RESULTS OF PATIENT CARE AFTER PANCREATOPHODEAL REMOVAL SURGERY AT VIET DUC FRIENDSHIP HOSPITAL IN 2024-2025. (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the results of patient care after pancreaticoduodenectomy at the On-Demand Treatment Department and the Oncology - Radiation Therapy Department of  Viet Duc Hospital. Method: Prospective descriptive study was conducted from 3/2024-3/2025 on 20 patients who met the selection criteria. Results: Average age of patients 61,25 (46-79). Male 85%, female 15%. Average surgery time (402.5 ± 115.9) minutes. Postoperative pain levels (VAS) at 6 hours; 12 hours and 24 hours were: (2.9 ± 0.8) points; (2.8 ± 0.7) points and (2.5 ± 0.6) points, respectively. Length of stay hospital (18.3 ± 4.9) days. Patients had flatus (4.3 ± 1.5) days; Time of gastric tube was removed (4.4 ± 1.6) days. Time of drainage removal was (13.4 ± 6.5) days. Patients mobilized early outside bed after surgery (2.6 ± 0.6) days. Patients were fed orally for (5.5 ± 1.4) days. Rate of postoperative complications: There were 2 (10%) cases of postoperative bleeding, of which 1 (5%) case required reoperation and 1 (5%) case required embolization. There was 1 (5%) case of postoperative infection requiring re-hospitalization.Conclusion: Postoperative patient care results were good in 90%, average in 5% and poor in 5%.
Keywords: care outcomes; post-pancreaticoduodenectomy